2012
DOI: 10.1371/journal.pone.0046773
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin 1 Is a miRNA Target in Neurons

Abstract: Mutations of the neurofibromin 1 gene cause neurofibromatosis type 1, a disease in which learning and behavioral abnormalities are common. The disease is completely penetrant but shows variable phenotypic expression in patients. The repertoire of regulatory interactions utilized by neurons to control neurofibromin 1 expression is poorly understood. Here, we examined the contribution of microRNAs into this regulatory network. Using reporter assays, we provided evidence that miR-128 and to a lesser extent miR-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
0
25
0
3
Order By: Relevance
“…Downregulation of neurofibromin may also result from the methylation of NF1 in cancer cells 78,79 . NF1 is also a target of micro-RNAs (mi RNAs); expression of miR-128 in neurons and miR-193b in head and neck squamous cell carcinoma cells decreased the levels of NF1 mRNA and neurofibromin 80,81 .…”
Section: Neurofibromin Regulation and Signallingmentioning
confidence: 99%
“…Downregulation of neurofibromin may also result from the methylation of NF1 in cancer cells 78,79 . NF1 is also a target of micro-RNAs (mi RNAs); expression of miR-128 in neurons and miR-193b in head and neck squamous cell carcinoma cells decreased the levels of NF1 mRNA and neurofibromin 80,81 .…”
Section: Neurofibromin Regulation and Signallingmentioning
confidence: 99%
“…In MAX-mutation-related PCC, however, these two microRNAs were underexpressed, thus MAX-mutations might result in a microRNA profile distinct from other PCC classes. miR-137 is underexpressed in several malignancies and its targets include mRNAs involved in gene expression regulation and signaling [82][83][84]. The oncogene c-MYC was found among the validated targets of miR-382 [85] that might be relevant as MAX (MYC-associated factor X) forms part of the c-MYC network [69].…”
Section: Micrornas In Pheochromocytomasmentioning
confidence: 99%
“…We found that the U6 snRNA was stable under BDNF treatment, so perhaps the issue is that U6 snRNA is affected by the retinoic acid treatment performed by Lim et al (2011) rather than their argument that it is inconsistently expressed. Furthermore, the miRNAs that they propose as endogenous controls are not suitable in a system looking at maturing neurons undergoing synaptogenesis as the expression of these miRNAs have been reported to change in developing neurons -for miR-103 (Paschou & Doxakis 2012) and in response to BDNF for miR-26b (Caputo et al 2011). Meanwhile contrary to Lim et al (2011), a study has reported that miR-106b expression changes during neuronal differentiation and it is involved in neurogenesis (Brett et al 2011), therefore this miRNA is also not a good candidate as an endogenous control.…”
Section: Resultsmentioning
confidence: 99%